Pemberian Insentif dan Motivasi Kerja dengan Mutu Pelayanan Perawat di Puskesmas Bangetayu Semarang - Syaifudin, Achmad; Hernawan, Satria Yosi; M Adinata, Ni Nyoman (UNIVERSITAS NGUDI WALUYO, 2020)
The quality of health services in Puskesmas and hospitals is the final product of complex interactions and dependencies between various components or aspects of service. Nursing service quality is a condition that can describe the level of perfection of a display of nursing service products that are provided bio-psycho-social-spiritual to sick and healthy individuals which are carried out based on established nursing care standards to suit customer desires.The Purpose of this study to analyze the relationship between incentives and work motivation with the quality of nurse services at the Bangetayu Public Health Center in Semarang.Type of this research is a quantitative study with the approach method used is cross sectional. Sampling by random sampling technique, obtained 41 respondents. Data collection using questionnaire instruments incentives, motivation and quality of nursing services. Research data were analyzed using chi square test.The results showed that the provision of incentives was largely satisfying (61%), the motivation of nurses was mostly positive (51.2%), and the quality of nursing services was mostly good (43.9%).The conclusion from this study shows that there is a relationship between providing incentives with the quality of nurse services at the Puskesmas Bangetayu Semarang p value (0.003) and there is a relationship between work motivation and the quality of nurse services at the Puskesmas Bangetayu Semarang p value (0.008).It is recommended that the Bangetayu Community Health Center pay attention to the provision of incentives and increase the motivation of Nurses to work at the Health Community Center of Bangetayu. Abtrak : Mutu pelayanan kesehatan di puskesmas dan rumah sakit adalah produk akhir dari interaksi dan ketergantungan yang rumit antara berbagai komponen atau aspek pelayanan. Mutu pelayanan keperawatan merupakan keadaan yang dapat menggambarkan tingkat kesempurnaan suatu tampilan dari produk pelayanan keperawatan yang diberikan secara bio-psiko-sosial-spiritual pada individu yang sakit maupun yang sehat yang dilakukan berdasarkan standar asuhan keperawatan yang telah ditetapkan guna menyesuaikan dengan keinginan pelanggan, tujuan akhirnya adalah terciptanya kepuasan pasien atau masyarakat. Penelitian ini bertujuan untuk menganalisa hubungan pemberian insentif dan motivasi kerja dengan mutu pelayanan perawat di Puskesmas Bangetayu Semarang. Jenis penelitian ini adalah penelitian kuantitatif dengan metode pendekatan yang digunakan adalah cross sectional. Pengambilan sampel dengan teknik random sampling, didapatkan 41 responden. Pengumpulan data menggunakan instrument kuesioner insentif, motivasi dan mutu pelayanan keperawatan. Data penelitian dianalisis menggunakan uji chi square. Hasil penelitian menunjukkan pemberian insentif sebagaian besar memuaskan (61%), Motivasi kerja Perawat sebagian besar positif (51,2%), dan mutu pelayanan keperawatan sebagian besar baik (43,9%). Kesimpulan dari penelitian ini menunjukkan ada hubungan antara pemberian insentif dengan mutu pelayanan perawat di Puskesmas Bangetayu Semarang p value (0,003) dan ada hubungan antara motivasi kerja dengan mutu pelayanan perawat di Puskesmas Bangetayu Semarang p value (0,008). Disarankan kepada Puskesmas Bangetayu memperhatikan pemberian insentif dan meningkatkan motivasi kerja Perawat di Puskesmas Bangetayu.